Socioeconomic Profile of Milk Producers in the Municipality of Olho D’agua das Flores, Alagoas, Brazil - Silva, José Crisólogo De Sales; Santos, Ademilson Neris Dos; Miranda, Pedro Alexandre Barbosa Pereira; Atroshenko, Andrei (American Journal of Trade and Policy, 2015)
Bovine milk is widely considered to be one of the most nutritious foods. It is rich in calcium and other ingredients, such as vitamins, protein and phosphorus. The municipality of Olho d´Água das Flores in the state of Alagoas, north-eastern Brazil is located in the microregion of Batalha of the mesoregion of Sertão Alagoano. The interviews for this study have been conducted over a period of 150 days between October 2011 and February 2012, whereby a questionnaire was used to collect the required information. Of the 41 producers interviewed, 37 were family farmers, as defined by the law nº 11.326/2006 of Brazil, relevant legislation currently regulating the classification of producers as “family farmers”, corresponding to 90% of the sample. Despite the properties of those interviewed exhibiting characteristics of differentiated production, continued high-quality technical assistance is the major necessity of the producers, hence the importance of understanding their socioeconomic profile and that of their properties.